THE EFFECT OF PROMOTION, LOCATION, AND PRODUCT ATTRIBUTES ON FRUIT SALAD PURCHASE DECISIONS - Julien Polin Timonia Br. L. Tobing; Effy Yuswita; Heptari Elita Dewi; Dina Novia Priminingtyas (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
The success of a business in today's globalized market depends on effective marketing and product innovation. This study aims to analyze consumers' assessment of various factors such as promotion, location, brand, price, taste, and packaging size, and their impact on purchasing decisions for Saladpilih.id fruit salad. The research method involves a quantitative approach and data collection through online questionnaires. A total of 94 samples were obtained using nonprobability sampling with the Slovin formula. The findings indicate that promotion, location, brand, price, taste, and packaging size were positively assessed by consumers, with purchasing decision receiving the highest score of 4.19 and promotion the lowest at 3.87. The study also reveals that promotion, location, brand, price, taste, and packaging size all influence consumer decisions when purchasing Saladpilih.id fruit salad.